Performance test method for manually simulating RTV interlayer defects
Through the performance testing method of manually simulating the defects of RTV interlayers, the impact of interlayer contamination after recoating on the performance of RTV coating is analyzed, and the problem of difficulty in systematic testing and analysis in the existing technology is solved, and the accurate evaluation of the performance of the new coating and the guarantee of safety of casing operation is achieved.
Patent Information
- Application Number
- CN202411722339.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to systematically test and analyze the effects of interlayer contamination on its performance after recoating, resulting in a decrease in hydrophobicity, reduced adhesion and anti-fouling flash performance of the new coating, which affects the operation safety of the casing.
A performance test method for artificially simulating RTV interlayer defects is proposed. By artificially aging and pretreatment of the coating test piece, actual RTV repair is simulated, interlayer defects are formed, adhesion level test and hydrophobicity test are carried out on the recoated coating to analyze the mechanism of the influence of interlayer defects on the performance of the new coating.
This method provides a more accurate and comprehensive state evaluation method, which can systematically analyze the impact of interlayer defects on the performance of new coatings, provide a theoretical basis for the evaluation of the operating status of the coating, and help ensure the operation of the sleeves.
Smart Images

Figure CN119619170A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of test methods, and in particular to a performance test method for artificially simulating RTV interlayer defects. Background Art
[0002] Insulators, commonly known as porcelain bottles, are insulators used to support conductors. Insulators can ensure sufficient insulation between conductors, crossarms and towers, and play an important role in overhead transmission lines, namely supporting conductors and preventing current from returning to the ground. Insulators should be able to withstand the vertical load and horizontal tension of the conductors during operation, and also withstand corrosion from the sun, rain, climate change and chemicals. Therefore, insulators must have both good electrical properties and sufficient mechanical strength. The quality of insulators is very important to the safe operation of the line.
[0003] In areas with serious pollution, in order to ensure the service life of insulators and the stability of electrical performance, a measure of spraying a layer of room temperature vulcanized silicone rubber (RTV) coating on the surface is widely adopted to ensure its insulation anti-pollution flashover, wet flashover and flashover performance. The operating environment of high-voltage bushings is more complicated than that of insulators, because in addition to conventional pollution deposition on the surface, there is also transformer oil infiltration, and the bushings also operate under a strong vertical component electric field. The above reasons lead to a very high incidence of pollution flashover accidents in transformer high-voltage bushings. Therefore, the RTV coating on the surface of the bushing is well representative and can be used as a research object for the operating characteristics of external insulation. After the bushings and insulators sprayed with RTV have been in operation for a period of time, the coating will gradually deteriorate under the influence of factors such as dirt and electric fields, and the performance will be manifested as damage, shedding and reduced hydrophobicity. At present, for bushings that have been coated with RTV coating, it is usually necessary to conduct a second anti-pollution spray on a regular basis. The installed bushings cannot be disassembled, and the old coating and dirt layer on the surface are difficult to clean in time. They can only be sprayed manually, and the coating quality is difficult to guarantee. This method mainly depends on the experience of the construction personnel. At the same time, there will inevitably be a dirt interlayer or air gap between the new and old coatings.
[0004] Interlayer contamination and air gaps may cause distortion of the electric field. In addition, the dielectric interface formed by interlayer contamination and air gaps may cause space charge polarization, which in turn causes local heating. The above factors may lead to aggravated local aging of the RTV coating, thereby reducing the adhesion of the bottom surface of the new coating. At the same time, interlayer contamination may affect the hydrophobicity of the new coating, ultimately making the anti-pollution flashover performance of the new coating ineffective, threatening the safe operation of the casing.
[0005] The current related research mainly focuses on the aging characteristics of coatings, the removal of old coatings and dirt, etc. The effect of interlayer dirt on the performance of RTV coatings needs further study. After re-coating RTV coatings, interlayer dirt may affect the performance of the new coating, resulting in reduced hydrophobicity, coating damage and shedding, and failure of anti-fouling flashover performance. There is no systematic test method analysis and research, and it is impossible to obtain the corresponding analysis results of interlayer dirt on RTV coating performance. Summary of the invention
[0006] In order to overcome the above problems, the purpose of the present invention is to provide a performance testing method for artificially simulating RTV interlayer defects. The testing method proposes a more accurate and comprehensive status evaluation method, which mainly processes the coating after artificial aging to obtain test pieces with different types of surfaces, and then simulates actual RTV repair, recoats the test pieces, and forms interlayer defects between the new and old coatings. The recoated coating is tested for adhesion grade and hydrophobicity, and various parameters are comprehensively analyzed to analyze the influence mechanism of interlayer defects on the performance of the new coating, providing a theoretical basis for the evaluation of the operating status of the coating.
[0007] The technical solution adopted by the present invention is:
[0008] A performance testing method for artificially simulating RTV interlayer defects comprises the following steps:
[0009] S01: Preparation of coating test piece samples,
[0010] Prepare several 3cm×3cm glass sheets, use the glass sheets to simulate the surface of the insulator, and use the spraying method to attach a certain thickness of RTV coating on the surface of the glass sheets to prepare multiple coating test pieces;
[0011] S02: Grouping of coating test pieces: The untreated coating test pieces simulate the clean surface and are recorded as the initial sample. The remaining coating test pieces are divided into common stained surface, oily surface, and damaged coating surface.
[0012] Use kaolin and sodium chloride to prepare artificial dirt with a certain degree of dirtiness, and evenly apply it on the surface of the coating test piece to simulate the common contaminated surface, which is recorded as the first group of control samples.
[0013] The coating test piece was soaked with insulating oil to simulate the oily surface, which was recorded as the second group of control samples.
[0014] Use a grid knife to cut the coating test piece to make the coating fall off to different degrees, simulating the damaged coating surface.
[0015] Recorded as the third group of control samples;
[0016] S03: Secondary RTV spraying,
[0017] The four groups of coating test pieces were placed in the laboratory for 24 hours to stabilize the coating test pieces. The coating test pieces were sprayed with RTV for the second time to obtain four groups of coating test pieces in different states.
[0018] S04: Testing the hydrophobicity of the coating specimens. The initial sample, the first group of control samples, the second group of control samples, and the third group of control samples are tested respectively. The test results of the first group of control samples, the second group of control samples, and the third group of control samples are compared with the results of the initial sample to determine the strength of the hydrophobicity.
[0019] S05: coating test piece adhesion grade test;
[0020] S06: Thermal accelerated aging test of the coating specimens. The coating specimen samples are placed in a constant temperature drying oven. Every 24 hours, the coating specimen samples are taken out and steps S04-S05 are repeated. Each group of coating specimens is tested, and the results are observed and recorded. The influence of the surface state parameters of the specimens on the performance of the recoated coating is analyzed to obtain the influence of the surface state parameters of the specimens on the performance of the recoated coating.
[0021] As a further description of the present invention, the hydrophobicity test in step S04 is determined by the size of the static contact angle θ, and the specific steps are as follows:
[0022] S041: drop the liquid onto the coating specimen after secondary RTV spraying by using the sessile drop method;
[0023] S042: Use a high-resolution camera to take images of the droplets and upload them to a computer;
[0024] S043: The software measures the static contact angle θ based on the uploaded image information.
[0025] As a further description of the present invention, the specific operation steps of the sessile drop method in step S041 and the capturing of the droplet image in step S042 are as follows:
[0026] During the measurement, a micro-injector was used to add droplets. A 4 μL drop of deionized water was dripped 5 mm above the sample surface. After waiting for 1 minute, a macro shot of the water drop was taken at a position parallel to the solid-liquid interface.
[0027] As a further description of the present invention, the specific steps of the adhesion level test in step S05 are:
[0028] S051: After cooling the coating specimen to room temperature, place it on a horizontal surface and test it perpendicular to the specimen surface;
[0029] S052: Use a grid knife to first draw multiple cutting lines, then draw the same number of cutting lines and make them perpendicular to each other;
[0030] S053: Pull out a piece of transparent tape at a constant speed, align the pulled tape with a set of score lines and keep it parallel to them, use your fingers to press the tape above the score lines and press it flat against the glass sheet;
[0031] S054: Tear off the transparent tape, observe the coating on the transparent tape, and compare the result with the reference table of GB / T 9286-1998 to obtain the adhesion grade.
[0032] As a further description of the present invention, after completing the adhesion level test, the influence of interlayer contamination on the new coating is analyzed based on the test pieces before and after the adhesion level test, and the specific steps are:
[0033] Use a camera to photograph the surface of the test piece before and after the adhesion test, observe the morphology of the surface of samples with different defects and the change in roughness, extract the roughness parameter from the sample photos as one of the status evaluation indicators, and indirectly infer the influence of interlayer defects on the adhesion of the recoating and the influence of interlayer contamination components on the structure of the new coating.
[0034] As a further description of the present invention, the aging rate in step S06 is estimated according to the time-temperature equivalence principle and established according to the Arrhenius formula, as shown in formula (1):
[0035]
[0036] Where K(T) is the reaction rate constant; B is the exponential factor; E is the surface activation energy, in J·mol -1 ; R is the molar gas constant, which is 8.314 J·K -1 ·mol -1 ; T is the thermodynamic temperature, K, e is a natural constant, about 2.718;
[0037] The relationship between rubber aging time t and aging temperature T is shown in formula (2):
[0038]
[0039] Where, t is the reaction time, in min; A is the constant term;
[0040] Assuming that the rubber is at temperature T1 and the required life span is t1, the accelerated thermal aging method is used to obtain: when the expected accelerated temperature is T2, the required accelerated aging time is t2. Substituting into formula (2), after equivalent transformation, formula (3) can be obtained:
[0041]
[0042] As a further description of the present invention, the measurement principle of the static contact angle used in the hydrophobicity study of the RTV coating is based on Young's equation, which describes the equilibrium relationship between a liquid droplet on a solid surface and the solid surface, as shown in the following equation (4):
[0043] γ GL cosθ=γ GS γ SL (4)
[0044] where γ GL is the gas-liquid surface tension, γ GS is the gas-solid surface tension, γ SL is the solid-liquid surface tension (N), θ is the contact angle, the smaller the static contact angle, the larger the contact area between the water droplet and the coating surface, and the worse the hydrophobicity of the RTV coating; conversely, the better the hydrophobicity.
[0045] As a further description of the present invention, the specific steps of analyzing and obtaining the influence of the surface state parameters of the test piece on the performance of the recoating coating in step S06 are: arranging the static contact angle, adhesion level, and surface roughness level parameters as the aging degree increases into a series, using a support vector data description algorithm,
[0046] According to the correlation between any two parameters, the weight of each parameter that determines the coating state is obtained according to formula (5):
[0047] ε(a, R)=R 2 (5)
[0048] Normalize the time series of each parameter, remove the dimension, and perform linear transformation according to their respective weights. The samples in the test process are divided into normal and aging states. The characteristic parameters of normal samples are imported into the support vector data description algorithm, and the target class is described in the region. The center a and the region radius R of the corresponding hypersphere are obtained. The generalized distance d between the sample to be tested and the center a is calculated using formula (6):
[0049] d=‖za‖=(z·z)-2∑ i α i (z·x i )-∑ i,j α i α j (x i ·x j )≤R (6)
[0050] If d≤R, the sample to be tested is considered to be in a normal state.
[0051] If d>R, the sample to be tested is considered to be in an aging state.
[0052] dR is an indicator that reflects the state of the sample to be tested.
[0053] When it is greater than 0, it indicates that the sample has deviated into the aging state. The larger the dR value, the worse the performance of the coating sample.
[0054] Beneficial effects of the present invention:
[0055] The present invention provides a performance testing method for artificially simulating RTV interlayer defects. The testing method proposes a more accurate and comprehensive state evaluation method. The method mainly processes the coating after artificial aging to obtain test pieces with different types of surfaces, simulates actual RTV repair, re-coats the test pieces, forms interlayer defects between the new and old coatings, performs adhesion grade tests and hydrophobicity tests on the re-coated coatings, comprehensively analyzes the influence mechanism of interlayer defects on the performance of the new coating by combining various parameters, and provides a theoretical basis for evaluating the operating state of the coating.
[0056] The present invention provides a performance testing method for artificially simulating RTV interlayer defects. In the steps of preparing and grouping coating test piece samples, the method innovatively performs artificial aging and pretreatment on the coating samples to obtain coating test pieces of different types and aging degrees, and then re-coats the surface to produce interlayer defects. Based on this, multiple macro and micro characteristic tests are performed, and the comprehensive test data obtained are compared to analyze and explore the hydrophobicity and adhesion characteristics of the new coating, understand the law and mechanism of the above-mentioned changing characteristics being affected by the original surface state, accumulate a large amount of experimental data as a standard for measuring the state of the re-coated coating, and further provide a theoretical basis for the maintenance of the casing RTV coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 A flow chart of a performance testing method for artificially simulating RTV interlayer defects proposed by the present invention;
[0058] Figure 2 A technical route flow chart of a performance testing method for artificially simulating RTV interlayer defects proposed by the present invention;
[0059] Figure 3 This is an appearance diagram of a control sample after the adhesion cross-cut test in a performance test method for artificially simulating RTV interlayer defects proposed by the present invention, wherein the left side shows the cross-cut test of the sample before aging, and the right side shows the cross-cut test of the sample after aging;
[0060] Figure 4 This is a schematic diagram of the static contact angle change characteristics of a control sample during the aging process in a performance testing method for artificially simulating RTV interlayer defects proposed by the present invention. The upper part is the change curve of the clean sample, and the lower part is the change curve of the sample after being immersed in transformer oil. DETAILED DESCRIPTION
[0061] The specific implementation of the present invention is described below in conjunction with the accompanying drawings and embodiments:
[0062] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the conditions under which the present invention can be implemented. Any structural modification, change in proportional relationship or adjustment of size should still fall within the scope of the technical contents disclosed in the present invention without affecting the effects and purposes that can be achieved by the present invention.
[0063] At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" cited in this specification are only for the convenience of description and are not used to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships should be regarded as the scope of implementation of the present invention without substantially changing the technical content.
[0064] like Figures 1 to 4 As shown, it shows a specific embodiment of the present invention:
[0065] Example
[0066] The present invention discloses a performance testing method for artificially simulating RTV interlayer defects, comprising the following steps:
[0067] S01: Preparation of coating test piece samples,
[0068] Prepare several 3cm×3cm glass sheets, use the glass sheets to simulate the surface of the insulator, and use the spraying method to attach a certain thickness of RTV coating on the surface of the glass sheets to prepare multiple coating test pieces;
[0069] S02: Grouping of coating test pieces: The untreated coating test pieces simulate the clean surface and are recorded as the initial sample. The remaining coating test pieces are divided into common stained surface, oily surface, and damaged coating surface.
[0070] Use kaolin and sodium chloride to prepare artificial dirt with a certain degree of dirtiness, and evenly apply it on the surface of the coating test piece to simulate the common contaminated surface, which is recorded as the first group of control samples.
[0071] The coating test piece was soaked with insulating oil to simulate the oily surface, which was recorded as the second group of control samples.
[0072] The coating specimens were cut with a grid knife to make the coating fall off to different degrees, simulating the damaged coating surface, which was recorded as the third group of control samples. The actual picture of the damaged coating surface in the actual test is shown in Figure 3 As shown;
[0073] S03: Secondary RTV spraying,
[0074] The four groups of coating test pieces were placed in the laboratory for 24 hours to stabilize the coating test pieces. The coating test pieces were sprayed with RTV for the second time to obtain four groups of coating test pieces in different states.
[0075] S04: Testing the hydrophobicity of the coating specimens. The initial sample, the first group of control samples, the second group of control samples, and the third group of control samples are tested respectively. The test results of the first group of control samples, the second group of control samples, and the third group of control samples are compared with the results of the initial sample to determine the strength of the hydrophobicity.
[0076] S05: coating test piece adhesion grade test;
[0077] S06: Thermal accelerated aging test of the coating specimens. The coating specimen samples are placed in a constant temperature drying oven. Every 24 hours, the coating specimen samples are taken out and steps S04-S05 are repeated. Each group of coating specimens is tested, and the results are observed and recorded. The influence of the surface state parameters of the specimens on the performance of the recoated coating is analyzed to obtain the influence of the surface state parameters of the specimens on the performance of the recoated coating.
[0078] In this embodiment, Figure 1 As shown in the figure, this test method proposes a more accurate and comprehensive condition assessment method, which mainly processes the coating after artificial aging to obtain test pieces with different types of surfaces, and then simulates actual RTV repair, recoats the test pieces, and forms interlayer defects between the new and old coatings. The recoated coating is tested for adhesion grade and hydrophobicity, and various parameters are combined to analyze the influence mechanism of interlayer defects on the performance of the new coating, providing a theoretical basis for the evaluation of the operating status of the coating.
[0079] In this embodiment, if Figure 2 As shown in the figure, it is the technical roadmap of the test method. In the steps of preparing and grouping the coating specimen samples, the coating samples are artificially aged and pretreated innovatively. Different means are used to obtain coating specimens of different types and aging degrees, namely, the first group of control samples in the test method have ordinary stained surfaces, the second group of control samples have oily surfaces, and the third group of control samples have damaged surfaces. After obtaining the corresponding samples, the surfaces are re-coated to produce interlayer defects. On this basis, a number of macroscopic and microscopic property tests are carried out, namely, the hydrophobicity test and adhesion grade test in the test method. The comprehensive test data are compared to analyze and explore the hydrophobicity and adhesion characteristics of the new coating, understand the laws and mechanisms of the influence of the above-mentioned changing characteristics on the original surface state, accumulate a large amount of experimental data as a standard for measuring the state of the re-coated coating, and then provide a theoretical basis for the maintenance of the casing RTV coating to achieve deeper research.
[0080] As a further description of the present invention, the hydrophobicity test in step S04 is determined by the size of the static contact angle θ, and the specific steps are as follows:
[0081] S041: drop the liquid onto the coating specimen after secondary RTV spraying by using the sessile drop method;
[0082] S042: Use a high-resolution camera to take images of the droplets and upload them to a computer;
[0083] S043: The software measures the static contact angle θ based on the uploaded image information.
[0084] Specifically, the specific operation steps of the sessile drop method in step S041 and the capturing of the droplet image in step S042 are as follows:
[0085] During the measurement, a micro-injector was used to add droplets. A 4 μL drop of deionized water was dripped 5 mm above the sample surface. After waiting for 1 minute, a macro shot of the water drop was taken at a position parallel to the solid-liquid interface.
[0086] In this embodiment, the size of the static contact angle θ is used to judge the hydrophobicity of the coating test piece. In the actual test, the measured values of the static contact angles of the three groups of control samples are shown in the following table:
[0087] Table 1 Hydrophobicity test data
[0088]
[0089] In the actual test, the contact angle variation with aging time is plotted based on the above experimental data as shown in the attached figure. Figure 4 As shown, the oil-containing state is the second group of control samples, and the oil-free state is the first group of control samples.
[0090] In this embodiment, the test data can be processed and analyzed according to the actual research content, and relevant research and verification can be carried out.
[0091] Specifically, the specific steps of the adhesion level test in step S05 are:
[0092] S051: After cooling the coating specimen to room temperature, place it on a horizontal surface and test it perpendicular to the specimen surface;
[0093] S052: Use a grid knife to first draw multiple cutting lines, then draw the same number of cutting lines and make them perpendicular to each other;
[0094] S053: Pull out a piece of transparent tape at a constant speed, align the pulled tape with a set of score lines and keep it parallel to them, use your fingers to press the tape above the score lines and press it flat against the glass sheet;
[0095] S054: Tear off the transparent tape, observe the coating on the transparent tape, and compare the result with the reference table of GB / T 9286-1998 to obtain the adhesion grade.
[0096] Specifically, after completing the adhesion level test, the effect of interlayer contamination on the new coating is analyzed based on the test pieces before and after the adhesion level test. The specific steps are:
[0097] Use a camera to photograph the surface of the test piece before and after the adhesion test, observe the morphology of the surface of samples with different defects and the change in roughness, extract the roughness parameter from the sample photos as one of the status evaluation indicators, and indirectly infer the influence of interlayer defects on the adhesion of the recoating and the influence of interlayer contamination components on the structure of the new coating.
[0098] In this embodiment, in the actual test, the measurement results of the adhesion level and roughness of the three groups of control samples are shown in the following table:
[0099] Table 2 Adhesion grade and roughness grade test data
[0100]
[0101] In this embodiment, the test data can be processed and analyzed according to the actual research content, and relevant research and verification can be carried out.
[0102] Specifically, the aging rate in step S06 is estimated according to the time-temperature equivalence principle and established according to the Arrhenius formula, as shown in formula (1):
[0103]
[0104] Where K(T) is the reaction rate constant; B is the exponential factor; E is the surface activation energy, in J·mol -1 ; R is the molar gas constant, which is 8.314 J·K -1 ·mol -1 ; T is the thermodynamic temperature, K, e is a natural constant, about 2.718;
[0105] The relationship between rubber aging time t and aging temperature T is shown in formula (2):
[0106]
[0107] Where, t is the reaction time, in min; A is the constant term;
[0108] Assuming that the rubber is at temperature T1 and the required life span is t1, the accelerated thermal aging method is used to obtain: when the expected accelerated temperature is T2, the required accelerated aging time is t2. Substituting into formula (2), after equivalent transformation, formula (3) can be obtained:
[0109]
[0110] In this embodiment, step S06 of the test method is specifically: thermal accelerated aging test of the coating specimen, placing the coating specimen sample in a constant temperature drying oven, taking out the coating specimen sample every 24 hours and repeating steps S04-S05, testing each group of coating specimens, observing and recording the results, and analyzing the influence of the surface state parameters of the specimen on the performance of the recoating coating.
[0111] In this step, accelerated thermal aging is required to simulate the long-term use of the coating test pieces of the three groups of control samples and the initial samples in actual applications, obtain corresponding test results, and provide a reliable basis for theoretical research.
[0112] Regarding the coating specimens estimated by the time-temperature equivalence principle in the accelerated thermal aging test, it can accurately simulate the state of the coating specimens in an outdoor environment for a long time, provide reliable simulation results, greatly shorten the test time, and provide reliable and effective support for theoretical research.
[0113] Specifically, the measurement principle of the static contact angle used in the hydrophobicity study of the RTV coating is based on Young's equation, which describes the equilibrium relationship between a liquid droplet on a solid surface and the solid surface, as shown in the following equation (4):
[0114] γ GL cosθ=γ GS γ SL (4)
[0115] where γ GL is the gas-liquid surface tension, γ GS is the gas-solid surface tension, γ SL is the solid-liquid surface tension (N), θ is the contact angle, the smaller the static contact angle, the larger the contact area between the water droplet and the coating surface, and the worse the hydrophobicity of the RTV coating; conversely, the better the hydrophobicity.
[0116] In this embodiment, the calculation and specific method of the static contact angle can refer to the prior art, such as the Chinese invention patent application number 201010147088.1, and the calculation is performed according to the disclosed method for calculating the static contact angle.
[0117] Specifically, the specific steps of analyzing and obtaining the influence of the surface state parameters of the test piece on the performance of the recoating coating in step S06 are: arranging the static contact angle, adhesion level, and surface roughness level parameters as the aging degree increases into a series, using a support vector data description algorithm,
[0118] According to the correlation between any two parameters, the weight of each parameter that determines the coating state is obtained according to formula (5):
[0119] ε(a, R)=R 2 (5)
[0120] Normalize the time series of each parameter, remove the dimension, and perform linear transformation according to their respective weights. The samples in the test process are divided into normal and aging states. The characteristic parameters of normal samples are imported into the support vector data description algorithm, and the target class is described in the region. The center a and the region radius R of the corresponding hypersphere are obtained. The generalized distance d between the sample to be tested and the center a is calculated using formula (6):
[0121] d=‖za‖=(z·z)-2∑ i α i (z·x i )-∑ i,j α i α j (x i ·x j )≤R (6)
[0122] If d≤R, the sample to be tested is considered to be in a normal state.
[0123] If d>R, the sample to be tested is considered to be in an aging state.
[0124] dR is an indicator that reflects the state of the sample to be tested.
[0125] When it is greater than 0, it indicates that the sample has deviated into the aging state. The larger the dR value, the worse the performance of the coating sample.
[0126] In this embodiment, the state of the sample is judged according to the relationship between the generalized distance d and the area radius R obtained by actual calculation, and the operating state of the coating sample is further subdivided according to the state index, which can achieve accurate evaluation of the operating state of the sample to be tested and reasonable prediction of the parameter change trend.
[0127] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
[0128] Many other changes and modifications may be made without departing from the concept and scope of the present invention.It should be understood that the present invention is not limited to the specific embodiments, and the scope of the present invention is defined by the appended claims.
Claims
1. A performance test method for artificially simulating RTV interlayer defects, characterized in that: The following steps are involved: S01: Preparation of coating test piece samples, Prepare several 3cm×3cm glass sheets, use the glass sheets to simulate the surface of the insulator, and use the spraying method to attach a certain thickness of RTV coating on the surface of the glass sheets to prepare multiple coating test pieces; S02: Grouping of coating test pieces: The untreated coating test pieces simulate the clean surface and are recorded as the initial sample. The remaining coating test pieces are divided into common stained surface, oily surface, and damaged coating surface. Use kaolin and sodium chloride to prepare artificial dirt with a certain degree of dirtiness, and evenly apply it on the surface of the coating test piece to simulate the common contaminated surface, which is recorded as the first group of control samples. The coating test piece was soaked with insulating oil to simulate the oily surface, which was recorded as the second group of control samples. The coating specimens were cut with a grid knife to make the coating fall off to different degrees, simulating the damaged coating surface, and recorded as the third group of control samples; S03: Secondary RTV spraying, The four groups of coating test pieces were placed in the laboratory for 24 hours to stabilize the coating test pieces. The coating test pieces were sprayed with RTV for the second time to obtain four groups of coating test pieces in different states. S04: Testing the hydrophobicity of the coating specimens. The initial sample, the first group of control samples, the second group of control samples, and the third group of control samples are tested respectively. The test results of the first group of control samples, the second group of control samples, and the third group of control samples are compared with the results of the initial sample to determine the strength of the hydrophobicity. S05: coating test piece adhesion grade test; S06: Thermal accelerated aging test of the coating specimens. The coating specimen samples are placed in a constant temperature drying oven. Every 24 hours, the coating specimen samples are taken out and steps S04-S05 are repeated. Each group of coating specimens is tested, and the results are observed and recorded. The influence of the surface state parameters of the specimens on the performance of the recoated coating is analyzed to obtain the influence of the surface state parameters of the specimens on the performance of the recoated coating.
2. A performance testing method for artificially simulating RTV interlayer defects according to claim 1, characterized in that: The hydrophobicity test in step S04 is determined by the size of the static contact angle θ, and the specific steps are as follows: S041: drop the liquid onto the coating specimen after secondary RTV spraying by using the sessile drop method; S042: Use a high-resolution camera to take images of the droplets and upload them to a computer; S043: The software measures the static contact angle θ based on the uploaded image information.
3. A performance testing method for artificially simulating RTV interlayer defects according to claim 2, characterized in that: The specific operation steps of the sessile drop method in step S041 and the capturing of the droplet image in step S042 are as follows: During the measurement, a micro-injector was used to add droplets. A 4 μL drop of deionized water was dripped 5 mm above the sample surface. After waiting for 1 minute, a macro shot of the water drop was taken at a position parallel to the solid-liquid interface.
4. The performance testing method for artificially simulating RTV interlayer defects according to claim 1, characterized in that: The specific steps of the adhesion level test in step S05 are: S051: After cooling the coating specimen to room temperature, place it on a horizontal surface and test it perpendicular to the specimen surface; S052: Use a grid knife to first draw multiple cutting lines, then draw the same number of cutting lines and make them perpendicular to each other; S053: Pull out a piece of transparent tape at a constant speed, align the pulled tape with a set of score lines and keep it parallel to them, use your fingers to press the tape above the score lines and press it flat against the glass sheet; S054: Tear off the transparent tape, observe the coating on the transparent tape, and compare the result with the reference table of GB / T 9286-1998 to obtain the adhesion grade.
5. A performance testing method for artificially simulating RTV interlayer defects according to claim 4, characterized in that: After completing the adhesion grade test, analyze the effect of interlayer contamination on the new coating based on the test pieces before and after the adhesion grade test. The specific steps are: Use a camera to photograph the surface of the test piece before and after the adhesion test, observe the morphology of the surface of samples with different defects and the change in roughness, extract the roughness parameter from the sample photos as one of the status evaluation indicators, and indirectly infer the influence of interlayer defects on the adhesion of the recoating and the influence of interlayer contamination components on the structure of the new coating.
6. A performance testing method for artificially simulating RTV interlayer defects according to claim 1, characterized in that: The aging rate in step S06 is estimated according to the time-temperature equivalence principle and established according to the Arrhenius formula, as shown in formula (1): Where K(T) is the reaction rate constant; B is the exponential factor; E is the surface activation energy, in J·mol -1 ; R is the molar gas constant, which is 8.314 J·K -1 ·mol -1 ; T is the thermodynamic temperature, K, e is a natural constant, about 2.718; The relationship between rubber aging time t and aging temperature T is shown in formula (2): Where, t is the reaction time, in min; A is the constant term; Assuming that the rubber is at temperature T1 and the required life span is t1, the accelerated thermal aging method is used to obtain: when the expected accelerated temperature is T2, the required accelerated aging time is t2. Substituting into formula (2), after equivalent transformation, formula (3) can be obtained:
7. A performance testing method for artificially simulating RTV interlayer defects according to claim 2, characterized in that: The static contact angle measurement principle used in the hydrophobicity study of the RTV coating is based on Young's equation, which describes the equilibrium relationship between a liquid droplet on a solid surface and the solid surface, as shown in the following equation (4): c GL cosθ=γ GS c SL (4) where γ GL is the gas-liquid surface tension, γ GS is the gas-solid surface tension, γ SL is the solid-liquid surface tension (N), θ is the contact angle, the smaller the static contact angle, the larger the contact area between the water droplet and the coating surface, and the worse the hydrophobicity of the RTV coating; conversely, the better the hydrophobicity.
8. The performance testing method for artificially simulating RTV interlayer defects according to claim 1, characterized in that: The specific steps of analyzing and obtaining the influence of the surface state parameters of the test piece on the performance of the recoating coating in step S06 are: arranging the static contact angle, adhesion level, and surface roughness level parameters as the aging degree increases into a series, using a support vector data description algorithm, According to the correlation between any two parameters, the weight of each parameter that determines the coating state is obtained according to formula (5): ε(a,R)=R 2 (5) Normalize the time series of each parameter, remove the dimension, and perform linear transformation according to their respective weights. The samples in the test process are divided into normal and aging states. The characteristic parameters of normal samples are imported into the support vector data description algorithm, and the target class is described in the region. The center a and the region radius R of the corresponding hypersphere are obtained. The generalized distance d between the sample to be tested and the center a is calculated using formula (6): d=||z-a||=(z·z)-2∑ i α i (z·x i )-∑ i,j α i α j (x i ·x j )≤R (6) If d≤R, the sample to be tested is considered to be in a normal state. If d>R, the sample to be tested is considered to be in an aging state. dR is an indicator that reflects the state of the sample to be tested. When it is greater than 0, it indicates that the sample has deviated into the aging state. The larger the dR value, the worse the performance of the coating sample.
Citation Information
Patent Citations
Apparatus and method for testing solid-liquid dynamic and static contact angles by actual liquid droplet method
CN101865807A
Performance degradation evaluation method for constant deceleration brake system of mine hoist
CN111723449A
Self-repairing anti-pollution flashover RTV coating and preparation method thereof
CN114539917A
Method for evaluating hot oil aging state of silicone rubber coating on surface of transformer bushing
CN115728217A